1995
DOI: 10.1074/jbc.270.1.425
|View full text |Cite
|
Sign up to set email alerts
|

Dominant Negative Mutations of the Guanylyl Cyclase-A Receptor

Abstract: Guanylyl cyclase-A (GC-A), a receptor for A-type natriuretic peptide (ANP), contains an extracellular ligand-binding domain, a single transmembrane domain, and intracellular protein kinase-like and cyclase catalytic domains. Expression of the putative cyclase catalytic region (HCAT) resulted in the formation of an active enzyme that migrated as a homodimer on gel filtration columns; treatment with sodium trichloroacetate caused dissociation of the dimer and a loss of cyclase activity. Co-transfection of HCAT a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
34
0

Year Published

1997
1997
2006
2006

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 72 publications
(34 citation statements)
references
References 31 publications
0
34
0
Order By: Relevance
“…These findings mirror data published by Chinkers and Wilson (21) demonstrating a lack of interaction between the extracellular domains of NPR-A and NPR-B. Furthermore, a dominant-negative mutant of NPR-A as well as an alternative splice variant of NPR-B acting in a dominant-negative manner have previously been used to study ANP and CNP physiology, providing evidence for the use of dominant-negative mutants in cell culture and transgenic animal models as a powerful method to study the specific function of NPRs (19,(22)(23)(24).…”
Section: Discussionmentioning
confidence: 99%
“…These findings mirror data published by Chinkers and Wilson (21) demonstrating a lack of interaction between the extracellular domains of NPR-A and NPR-B. Furthermore, a dominant-negative mutant of NPR-A as well as an alternative splice variant of NPR-B acting in a dominant-negative manner have previously been used to study ANP and CNP physiology, providing evidence for the use of dominant-negative mutants in cell culture and transgenic animal models as a powerful method to study the specific function of NPRs (19,(22)(23)(24).…”
Section: Discussionmentioning
confidence: 99%
“…This generated a cDNA fragment coding for a cytoplasmic domain of NPRA containing the catalytic fragment of the guanylate cyclase domain. It has been shown that this fragment codes for a soluble cytoplasmic protein that has constitutive guanylate cyclase activity in transfected COS cells (16,17). This cDNA fragment was cloned downstream of a 5.8-kb fragment of the ␣-myosin heavy chain gene promoter (generous gift from J. Robbins, University of Cincinnati) and upstream of a portion of the rabbit ␤-globin gene containing an intron and a polyadenylation signal.…”
Section: Methodsmentioning
confidence: 99%
“…Other studies using gel filtration instead of co-immunoprecipitation concluded that the intracellular portion is also involved in receptor dimerization (18). Furthermore, it was shown that this interaction is mediated by a hinge region located between the KHD and GC regions (18,19).…”
mentioning
confidence: 99%